ChemInform Abstract: From Anilines to Isatins: Oxidative Palladium‐Catalyzed Double Carbonylation of C—H Bonds. Issue 25 (5th June 2015) - Li, Wu; Duan, Zhengli; Zhang, Xueye; Zhang, Heng; Wang, Mengfan; Jiang, Ru; Zeng, Hongyao; Liu, Chao; Lei, Aiwen
Abstract: A novel palladium‐catalyzed C—H double carbonylation introduces two adjacent carbonyl groups for the synthesis of isatins from readily available anilines.